'A wonderful advertisement for our country'. New Zealand tourism film's dynamics of circulation 1923–1989. Issue 2 (3rd May 2020) - Bonelli, Diego
ABSTRACT: The systematic intertwining of filmmaking, national publicity and tourism promotion in New Zealand dates back to 1901, when the Department of Tourist and Health Resorts began hiring filmmakers to shoot some of the country's most iconic locations. Since then, the role government-led film production companies played in national tourism marketing grew increasingly stronger through both the Government Publicity Office (1923–1941) and the National Film Unit (1941–1989) eras. During the existence of these two government-led film production companies, the carefully planned production and circulation of tourism films celebrating New Zealand tourist attractions and promoting the country both domestically and overseas was, with the exception of the World War II period, a recurring element. Through the examination of archival documents related to New Zealand tourism film production such as production papers, government documents, correspondence between stakeholders, newspaper articles and an interview with NFU's director Hugh Macdonald, this article aims to retrace New Zealand tourism films' modes and patterns of circulation and platforms of distribution from the establishment of the Government Publicity Office in 1923 to the closure of the National Film Unit in the late 1980s.